Differential methylation of the type 2 diabetes susceptibility locus KCNQ1 is associated with insulin sensitivity and is predicted by CpG site specific genetic variation. (February 2019) - Shah, Ushma J.; Xie, Weijia; Flyvbjerg, Allan; Nolan, John J.; Højlund, Kurt; Walker, Mark; Relton, Caroline L.; Elliott, Hannah R.; ,
Abstract: Aims: Epigenetic mechanisms regulate gene expression and may influence the pathogenesis of type 2 diabetes through the loss of insulin sensitivity. The aims of this study were to measure variation in DNA methylation at the type 2 diabetes locus KCNQ1 and assess its relationship with metabolic measures and with genotype. Methods: DNA methylation from whole blood DNA was quantified using pyrosequencing at 5 CpG sites at the KCNQ1 locus in 510 individuals without diabetes from the 'Relationship between Insulin Sensitivity and Cardiovascular disease' (RISC) cohort. Genotype data was analysed at the same locus in 1119 individuals in the same cohort. Insulin sensitivity was assessed by euglycaemic-hyperinsulinaemic clamp. Results: DNA methylation at the KCNQ1 locus was inversely associated with insulin sensitivity and serum adiponectin. This association was driven by a methylation-altering Single Nucleotide Polymorphism (SNP) (rs231840) which ablated a methylation site and reduced methylation levels. A second SNP (rs231357), in weak Linkage Disequilibrium (LD) with rs231840, was also associated with insulin sensitivity and DNA methylation. These SNPs have not been previously reported to be associated with type 2 diabetes risk or insulin sensitivity. Conclusion: Evidence indicates that genetic and epigenetic determinants at the KCNQ1 locus influence insulin sensitivity.